Suicidal ideation, suicidal behaviors, and attitudes towards suicide of adolescents enrolled in the Alternative Learning System in Manila, Philippines—a mixed methods study - Crystal Amiel M. Estrada; Daisuke Nonaka; Ernesto R. Gregorio; Cynthia R. Leynes; Ronald T. del Castillo; Paul Michael R. Hernandez; Tatsuro Hayakawa; Jun Kobayashi (Tropical Medicine and Health, 2019)
Abstract Background Globally, suicide is a significant cause of death among adolescents. Previous studies conducted in high-income countries suggest that students in alternative schools are more likely to engage in suicidal behaviors than those in formal schools. This study aimed to document suicidal ideation and behaviors among adolescent learners enrolled in the Alternative Learning System (ALS) in Manila, Philippines. Methods A mixed methods study was conducted in 24 ALS centers in the city of Manila. ALS centers were stratified according to congressional district and selected using probability proportionate sampling. A cross-sectional survey to determine attitudes towards suicide and prevalence of suicidal ideation and behaviors was administered to 171 learners aged 13 to 17 years old. In-depth interviews with 18 teachers and 12 learners were conducted to explore the school psychosocial environment’s role on learners’ suicidal ideation and behaviors. Exploratory factor analysis was used to extract attitude factors. Fisher’s exact test and Student’s t-test were used to identify differences in sociodemographic characteristics and attitudes towards suicide between learners with or without suicidal ideation or behaviors. Qualitative data were analyzed using thematic analysis. Results Non-specific active thoughts were the most common type of lifetime suicidal ideation (40.9%) while passive ideation was the most common in the past month (13.5%). Aborted suicide attempt was the most frequent behavior in both lifetime (16.4%) and in the past month (4.7%). Non-fatal suicide attempt in the past month was 2.3%, reaching 12.9% for the entire lifetime. Age, sex, education, and attitudes towards suicide were significantly associated with suicidal ideation or behavior. Thematic analysis showed five themes: (1) fostering belongingness, (2) securing learners’ safety, (3) teaching philosophy, (4) teacher and learner beliefs towards suicidal behavior, and (5) availability of school-offered and community-based services. Conclusion Suicidal ideation and behaviors are prevalent among adolescent ALS learners. This study also showed a significant difference in attitudes towards suicide and sociodemographic characteristics between learners with and without suicidal ideation behaviors. It also suggests that the school psychosocial environment, through social norms and learner-teacher interactions, can potentially prevent progression of suicidal ideation to behavior, influence help-seeking, and promote mental health among learners.